Chapter 10 Sustainability, Public Security, and Privacy Concerns Regarding Central Bank Digital Currency (CBDC) - Rybski, Robert (Taylor & Francis, 2024)
Around 100 central banks currently research or develop their own central bank digital currency (further CBDC). Two projects recently moved into the production phase. The introduction of CBDC by at least one major central bank in the coming years seems unavoidable, which would form a tipping point. CBDC would then enter the mainstream of the banking sector. This trend requires assessing CBDC projects broader than the central banks do. This chapter considers concerns regarding the introduction of CBDC and its design criteria. Addressing those issues at an early stage allows us to mitigate them. The most obvious concern concerns the central bank money's public security in the era of growing cyber threats. The other evident concern concerns privacy. However, one particular angle of discussions on CBDC does not get enough attention - sustainability. This chapter assesses whether and how current CBDC projects include sustainability, public security, and privacy. It then addresses areas worth further development to increase the implementation of sustainability by the central banks. Finally, this chapter reconstructs a design of CBDC that would be most desired from the perspective of sustainability, public security, and privacy, showing how taking those perspectives into consideration influences social acceptance of CBDC.